On multivariate orthogonal polynomials and elementary symmetric functions - Bracciali, Cleonice F. [UNESP]; Piñar, Miguel A. (Springer Nature, 2023)
We study families of multivariate orthogonal polynomials with respect to the symmetric weight function in d variables Bγ(x)=∏i=1dω(xi)∏i<j|xi-xj|2γ+1,x∈(a,b)d,for γ> - 1 , where ω(t) is an univariate weight function in t∈ (a, b) and x= (x1, x2, … , xd) with xi∈ (a, b). Applying the change of variables xi, i= 1 , 2 , … , d, into ur, r= 1 , 2 , … , d, where ur is the r-th elementary symmetric function, we obtain the domain region in terms of the discriminant of the polynomials having xi, i= 1 , 2 , … , d, as its zeros and in terms of the corresponding Sturm sequence. Choosing the univariate weight function as the Hermite, Laguerre, and Jacobi weight functions, we obtain the representation in terms of the variables ur for the partial differential operators such that the respective Hermite, Laguerre, and Jacobi generalized multivariate orthogonal polynomials are the eigenfunctions. Finally, we present explicitly the partial differential operators for Hermite, Laguerre, and Jacobi generalized polynomials, for d= 2 and d= 3 variables.
Keywords: Elementary symmetric functions; Multivariate orthogonal polynomials; Symmetric polynomials